Mitigasi Risiko Dan Jaminan Social Bagi Penyelenggara Pemilu 2024 - Yusrang (Journal of Law and Administrative Science, 2023)
Abstract; It is the constitutional mandate of the Republic of Indonesia to make elections a means of popular sovereignty and to be held every 5 years. Reflecting on the 2019 experience, elections were held simultaneously based on the Constitutional Court Decision MK No. 14/PUU-XI/2013 which simultaneously held presidential elections and national parliamentary elections and was followed up in Law No. 7 of 2017 concerning General Elections which also simultaneously held local parliamentary elections (provincial and district/city DPRD) along with presidential-vice presidential elections and parliamentary elections national (DPR and DPD). This assignment is directly proportional to the workload carried out by election organizers. For this reason, there is a need for health insurance and social security for election organizers as risk mitigation. In the future 2024 elections it has been anticipated through a strict recruitment process for election organizers and for social security the Presidential Instruction of the Republic of Indonesia has been issued Number 2 of 2021 concerning Optimizing the Implementation of the Employment Social Security Program.